Comparative study between sequential chemoradiotherapy with concurrent chemoradiotherapy for unresectable locally advanced esophageal cancer - Arifeen, Muhammad Adnan; Sumsuzoha, A. Z. M.; Haque, M. Ershadul; Sweet, Ahammad Al Mamun; Bhuiyan, M. Ruhul Amin; Bayzid, Khandakar MD Rezwan; Bhowmik, Nayan; Das, Barun Kumar (International Journal of Research in Medical Sciences, 2025)
Background: Esophageal squamous cell carcinoma (ESCC) is a prevalent malignancy in South Asia with a high burden of unresectable cases at presentation. Chemoradiotherapy remains the mainstay of treatment, with concurrent chemoradiotherapy (CCRT) offering improved tumor control but at the cost of higher toxicity. The study aimed to compare the clinical efficacy and treatment-related toxicities of sequential chemoradiotherapy (SCRT) versus concurrent chemoradiotherapy (CCRT) in patients with unresectable locally advanced ESCC. Methods: This quasi-experimental study was conducted at Khwaja Yunus Ali Medical College and Hospital, Sirajganj, from January 2020 to June 2021. A total of 62 patients with histologically confirmed unresectable ESCC were randomly assigned to two groups: Arm A (CCRT) and Arm B (SCRT), with 31 patients in each group. Results: The baseline characteristics were comparable between the two arms. At 24 weeks, complete response rates were slightly higher in Arm A (51.61%) than in Arm B (41.93%), though not statistically significant (p>0.05). Toxicity analysis revealed a significantly higher incidence of Grade III esophagitis in the CCRT group (22.58% vs 3.23%; p=0.001). Hematologic and late radiation-related toxicities were also more frequent in Arm A. Weight loss and need for nutritional support (e.g., NG tube) were more common in the CCRT group, although not statistically significant. Conclusions: While both treatment strategies showed similar tumor response rates, SCRT was associated with a more favorable toxicity profile. Thus, SCRT may serve as an effective and safer alternative for patients with unresectable locally advanced ESCC, especially in resource-constrained settings or among patients with borderline performance status.